INTERFIRM COOPERATION AND INFORMATION SHARING THROUGH INTERLOCKING DIRECTORATES - Mohammed Belal UDDIN (Management & Marketing, 2012)
When firms engage in cooperative efforts, interfirm relations get particular interest to be studied. A direct interlock occurs when an executive or director of one firm sits on the board of another firm, and an indirect interlock occurs when two firms have directors or executives who sit on the board of a third firm. The three commonly used theoretical models such as social network theory, learning theory, and theory of strategic choice are more relevant for the formation and management of interlocking directorates. Uncertainty, resource scarcity, mutual trust, dependency, etc. influence the formation of interlocking directorates. Consequently, interlocking directorates allow sharing of information and overall cooperation between partners through learning, collaboration, networking, and effective relationship, etc. Proper management of interlocking directorates requires communication and collaboration among partners that enhance exchange of knowledge and cooperation.